Substantial Need for Preexposure Prophylaxis Among Men Who Have Sex With Men in Hanoi, Vietnam. Issue 5 (May 2021) - Bhatia, Ramona; Le Minh, Giang; An, Ly Thanh; Thai, Truc Thanh; Bui, Hao; Ngoc, Lung Bich; Vu, Diep; Abdul-Quader, Abu
Abstract : Of 717 HIV-negative men who have sex with men in Hanoi, 537 (72.2% [66.6%–77.3%]) had ≥1 PrEP indication, signaling a substantial PrEP need in this community. The most common indications were condomless anal intercourse and sexually transmitted infection. Abstract: We used data from the Health in Men—Hanoi cohort to determine the proportion of HIV-negative men who have sex with men with PrEP indications in Hanoi. Among 717 men who have sex with men, 537 (72.2% [66.6%–77.3%]) had ≥1 PrEP indication, signaling a substantial need for PrEP scale-up. Condomless anal intercourse was the most frequent indication (68.7% [60.3%–76.1%]), followed by previous/current sexually transmitted infection (59.4% [51.0%–67.2%]).